2021
DOI: 10.1002/agj2.20547
|View full text |Cite
|
Sign up to set email alerts
|

Identification and verification of rhizosphere indicator microorganisms in tobacco root rot

Abstract: This study aimed to investigate the characteristics of the microbial community in the rhizosphere of tobacco (Nicotiana tabacum L.) and explore the potential microbiological indicators of tobacco root rot Rhizosphere soils of healthy and diseased tobacco over different continuous cropping years were sampled, and total DNA was extracted from the soils. Afterward, 16S rRNA combined with internal transcribed spacer gene sequencing was used to study the differences in microbial communities in the rhizosphere. A po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…and Streptomyces have been reported as suppressors of rhizosphere fungi that are pathogenic to other plant species, such as Fusariumoxysporum, Rhizoctonia solani, and Verticillium dahliae (CHAURASIA et al, 2005;ISLAM et al, 2012;CAO et al, 2016;SIEGEL-HERTZ et al, 2018;YAO et al 2020). These species were also reportedin this study, so future analyses should be carried out to evaluate the biological control capabilities of these bacterial members.…”
Section: Discussionmentioning
confidence: 99%
“…and Streptomyces have been reported as suppressors of rhizosphere fungi that are pathogenic to other plant species, such as Fusariumoxysporum, Rhizoctonia solani, and Verticillium dahliae (CHAURASIA et al, 2005;ISLAM et al, 2012;CAO et al, 2016;SIEGEL-HERTZ et al, 2018;YAO et al 2020). These species were also reportedin this study, so future analyses should be carried out to evaluate the biological control capabilities of these bacterial members.…”
Section: Discussionmentioning
confidence: 99%
“…This cluster encompasses a broader range of genera, predominantly comprising PGPR species or indicators of soil health. Notable genera in this cluster include Bdellovibrio, Massilia, Phormidium, Phormidesmis, Acidovorax, Flavobacterium, Olivibacter, Arthrobacter, Kocuria, Noviherbaspirillum, and Nafulsella, previously mentioned as beneficial microorganisms; as well as Dyadobacter, known as a PGPR commonly present in the rhizosphere that enhances crop yield [81]; Streptomyces, commonly found in plant microbiomes with PGPR characteristics [82]; Rubrobacter, associated with potassium absorption and soil health [69,83]; Virgibacillus, housing halophytic PGPR species [84,85]; Pseudonocardia, a P-solubilizing bacterium and disease-suppressive bacterial agent [86,87]; Nocardioides, possessing PGPR capabilities to mitigate saline stress conditions [88,89]; and Promicromonospora, a PGPR producing gibberellins and mitigating the adverse effects of salinity and osmotic stress [90,91].…”
Section: Discussionmentioning
confidence: 99%
“…Little information is available about the genus Kaistobacter; however, some studies have reported species of this genus as being associated with active disease suppression in the rhizosphere of tobacco plants [21,37]. Moreover, genera including Bacillus, Rubrobacter, and Streptomyces have been reported as suppressors of rhizosphere fungi that are pathogenic to other plant species, such as Fusarium oxysporum, Rhizoctonia solani, and Verticillium dahliae [9,12,30,56,73]. These species were also found in this study, so future analyses should be carried out to evaluate the biological control capabilities of these bacterial members.…”
Section: Discussionmentioning
confidence: 99%